Genome-wide association analysis of grain iron and zinc in rice grown under agroclimatic sites with contrasting soil iron status - Sonu,; Kumar, Amit; Singh, Vikram Jeet; Bhowmick, Prolay Kumar; Nandakumar, Shekharappa; Yadav, Sunaina; Krishnan, Subbaiyan Gopala; Ellur, Ranjith Kumar; Bollinedi, Haritha; Singh, Ashok Kumar; Vinod, Kunnummal Kurungara (Frontiers in Plant Science, 2025)
IntroductionIron (Fe) content in soil can influence rice cultivation, inciting responses ranging from deficiency to toxicity. Fe toxicity is a major constraint, particularly in areas where acidic soils predominate. Grain Fe content along with Zn is a major contemporary breeding objective in rice in order to tackle micronutrient deficiency. There is no information available on the influence of soil Fe levels, normal and excess, can influence grain micronutrient contents, particularly in rice genotypes that are tolerant to excess soil Fe.MethodsIn this study, a subset of 170 rice germplasm lines from the 3K panel were evaluated for grain Fe and Zn concentrations in brown rice across three different locations. Additionally, the response of these lines to Fe toxicity was assessed at one location.ResultsSignificant phenotypic variation for both traits was observed. Fe toxicity led to increased grain Fe content but decreased Fe uptake efficiency (IAE), suggesting an adaptive mechanism to limit excess Fe absorption in the rhizosphere. Five significant single-nucleotide polymorphisms (SNPs) associated with grain Fe (qGFe1.1ADT, qGFe2.1BPN-S, qGFe8.1ADT, qGFe12.1ADT, and qGFe12.2BPN-N) were identified on chromosomes 1, 2, 8, and 12, while one SNP associated with grain Zn (qGZn12.1BPN-N) was detected on chromosome 12. These SNPs co-localized with major genes and QTLs involved in heavy-metal homeostasis and transport, including OsMT2D and Os12g0435000. Superior haplotypes for two candidate genes were identified, with the analysis revealing their frequencies and allelic effects in different subgroups. Two marker-trait associations (MTAs), qGFe12.1ADT and qGZn12.1BPN-N, were validated in an F2:3 population using linked SSR markers.DiscussionThese validated MTAs provide valuable genetic resources for biofortification breeding programs aimed at increasing Fe and Zn concentrations in rice grains, addressing micronutrient deficiencies among rice-dependent populations.